Which Factors, Smoking, Drinking Alcohol, Betel Quid Chewing, or Underlying Diseases, Are More Likely to Influence the Severity of COVID-19? - Zhong, Rui; Chen, Lingxia; Zhang, Qiong; Li, Binbin; Qiu, Yanfang; Wang, Wei; Tan, Dongyi; Zou, Yanhui (Frontiers in Physiology, 2021)
Background The global outbreak of the COVID-19 pandemic occurred in late 2019 and early 2020. The factors that influence the severity of the disease should be of clinical concern. Existing findings on the effects of smoking on COVID-19 are also controversial and need to be confirmed by further research. In addition, the effects of alcohol consumption and betel quid chewing on COVID-19 are unclear. Purpose To study the demographic characteristics of COVID-19 patients and the effects of smoking, drinking, betel quid chewing, and underlying diseases on the severity of COVID-19. Methods A retrospective study was conducted on 91 confirmed cases of COVID-19 hospitalized in a hospital in Yueyang, Hunan Province, China from January 21 to March 8, 2020. The patient demographic data, smoking, drinking and betel quid chewing status, and underlying disease were extracted from the patient EMR and completed with telephone interviews by the researcher. The chi-square test was used to conduct a univariate analysis of the factors influencing the clinical classification of COVID-19, and ordinal logistic regression analysis was used to identify the factors related to the clinical typing of COVID-19. Results Ninety-one hospitalized COVID-19 patients were included in the study. The results showed that the rates of smoking, drinking and betel quid chewing were 15.4%, 26.4% and 7.1%, respectively, with no statistical significance with the clinical typing of COVID-19 (P > 0.05). The study found that patients with underlying diseases such as diabetes (OR=7.740,95% CI:1.000-60.740, P=0.050), source of infection (OR=0.180, 95% CI:0.030-0.980, P=0.049), and retired/unemployed (OR= 29.430, 95% CI: 1.050 – 822.330, P=0.047) had more severe COVID-19 infection. Conclusion This study showed that the clinical classification of COVID-19 was associated with patients with diabetes, source of infection, and retired/unemployed. Therefore in the clinical practice of COVID-19 should be more concern these factors. Although no statistical significance was found in smoking, drinking alcohol, betel quid chewing and severity of COVID-19 patients, more studies have confirmed that are risk factors for underlying diseases in the population. Health authorities should formulate policies to publicize the harmful effects of smoking, drinking and betel nut chewing and promote a healthy lifestyle.